Pengaruh Career Development, Self Efficacy, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Pacific Garment dengan Motivasi Kerja Sebagai Variabel Intervening - Kristina Ayu Oktaviani; Nur Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the effect of Career Development, Self-Efficacy, and Work Environment on Employee Performance at PT. Pacific Garment, with Work Motivation as an intervening variable. A quantitative approach was used, involving 50 employees as the sample. Data were collected via questionnaires on career development, self-efficacy, work environment, work motivation, and employee performance. The analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with Smart PLS 3 software. The results show that Career Development has a positive effect on work motivation but does not significantly affect performance. Self-Efficacy positively influences performance but not motivation. The work environment positively impacts motivation, but not performance. Work motivation has a positive effect on performance but does not mediate other factors. These findings suggest that while motivation improves performance, other factors' influence on performance is weak. The study's limitations include its reliance on questionnaires and a focus on one company. Future research should explore diverse indicators, use qualitative methods, and involve other organizations.